Comparison of Traditional and Novel Self‐Report Measures to an Alcohol Biomarker for Quantifying Alcohol Consumption Among HIV‐Infected Adults in Sub‐Saharan Africa. (4th July 2015) - Asiimwe, Stephen B.; Fatch, Robin; Emenyonu, Nneka I.; Muyindike, Winnie R.; Kekibiina, Allen; Santos, Glenn‐Milo; Greenfield, Thomas K.; Hahn, Judith A.
<x xml:space="preserve">Abstract</x> Background In Sub‐Saharan Africa (SSA), HIV‐infected patients may underreport alcohol consumption. We compared self‐reports of drinking to phosphatidylethanol (PEth), an alcohol biomarker. In particular, we assessed beverage‐type‐adjusted fractional graduated frequency (FGF) and quantity frequency (QF) measures of grams of alcohol, novel nonvolume measures, and the Alcohol Use Disorders Identification Test‐Consumption (AUDIT‐C). Methods We analyzed cohort entry data from the Biomarker Research of Ethanol Among Those with HIV cohort study (2011 to 2013). Participants were HIV‐infected past‐year drinkers, newly enrolled into care. Self‐report measures included FGF and QF grams of alcohol, the AUDIT‐C, number of drinking days, and novel adaptations of FGF and QF methods to expenditures on alcohol, time spent drinking, and symptoms of intoxication. PEth levels were measured from dried blood spots. We calculated Spearman's rank correlation coefficients of self‐reports with PEth and bias‐corrected bootstrap 95% confidence intervals (CIs) for pairwise differences between coefficients. Results A total of 209 subjects (57% men) were included. Median age was 30; interquartile range (IQR) 25 to 38. FGF grams of alcohol over the past 90 days (median 592, IQR 43 to 2, 137) were higher than QF grams (375, IQR 33 to 1, 776), p < 0.001. However, both measures were moderately correlated with PEth: ρ = 0.58, 95% CI 0.47 to 0.66 for FGF grams and 0.54, 95% CI 0.43 to 0.63 for QF grams (95% CI for difference −0.017 to 0.099, not statistically significant). AUDIT‐C, time drinking, and a scale of symptoms of intoxication were similarly correlated with PEth (ρ = 0.35 to 0.57). Conclusions HIV‐infected drinkers in SSA likely underreport both any alcohol consumption and amounts consumed, suggesting the need to use more objective measures like biomarkers when measuring drinking in this population. Although the FGF method may more accurately estimate drinking than QF methods, the AUDIT‐C and other nonvolume measures may provide simpler alternatives.